2012
DOI: 10.1002/srin.201200114
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Activity Calculations of Molten Steel: Comparison With Measured Results

Abstract: This study sets out to find some model/s that could calculate the closest oxygen activity of molten steel to the measured oxygen activity in an ASEA-SKF ladle furnace. Ten steel heats grade SAE 52100 were chosen, the oxygen activities of the molten steel after vacuum degassing process were measured, then by means of two different equations and one computer programs the theoretical oxygen activities were calculated and compared to the measured results. In order to calculate the activities of Al 2 O 3 in the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Table 5 present the measured as well as calculated amount of oxygen in molten steel. Extensive information about the reasons behind choosing these calculations are presented in another articles [7][8][9]; these calculation methods concluded to generate the most meaningful and comparable results to the measured results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 present the measured as well as calculated amount of oxygen in molten steel. Extensive information about the reasons behind choosing these calculations are presented in another articles [7][8][9]; these calculation methods concluded to generate the most meaningful and comparable results to the measured results.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that during the vacuum degassing process Aluminium of the molten steel it moved to the top slag thus increasing the Al/Ca ratio toward the equilibrium of the Al 2 O 3 -CaO binary phase. This subject is comprehensively analysed and discussed on other studies showing the importance of Alumina capacity if the synthetic top slag in inclusion removal [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A necessary step in the model development is its validation by the comparison of predictive results with experimen- Concerning about CaO-SiO 2 -Al 2 O 3 -MgO quaternary system, Kamrooz Riyahimalayeri et al measured the oxygen activities in molten steel after vacuum degassing for 10 samples. 32) Figure 5 presents the calculated oxygen activities of the ten different sampled heats versus their respective sample numbers. As could be seen six different combinations of models including this model were applied in order to present oxygen activities of molten steel after degassing process.…”
Section: Validation Of Modelmentioning
confidence: 99%
“…In this case, especially the availability of data for oxide activities in fluoride based slags is very limited in the current literature. Referring to pure oxide systems, consisting mainly of CaO and Al 2 O 3 , Riyahimalayeri[8] et al have summarized different approaches for calculating the activity of Al 2 O 3 . Further suggestions of Mitchell[9] include the assumption for systems containing less than 70 wt.-% CaF 2 that calcium fluoride could be considered as an inert diluent.…”
mentioning
confidence: 99%